Composting of Oil Palm Empty Fruit Bunches with Trichoderma and Organic Nitrogen Supplementation and the Effects of the Compost on Growth of Tomato and Corn - Mukhlis (2006)
Currently, Malaysia has 3.875 million ha of oil palm plantation. In total, about 90 million t of renewable biomass (trunks, fronds, shells, palm press fibre, and the empty b i t bunches) are produced annually. The empty h i t bunches (EFB) represent about 9 % of this total. EFB are the residue afler the fresh h i t bunches (FFB) harvested fiom the oil palm are processed by the mill. About 22% of the processed FFB ends up as EFB which is a good source of macro and micro nutrients. In order to add value and to reduce the volume for easier application, composting of EFB has become increasingly popular. By composting the properties of the organic matter are easier to handle, more suitable as soil conditioners and organic fertilizer and do not adversely affect the environment. However, composting of EFB is generally time consuming. Therefore, the ability of Trichoderma and organic N was tested as activators that can accelerate the maturity and enhance the quality of oil palm EFB compost within a shorter period of time. In this study, screening of Trichoderma isolates was done in vitro for their ability to decompose cellulose and production of polyphenol oxidase. Six isolates were iii selected to further study the in vitro decomposition of EFB and their phytopathogenicity against seed germination. Biodegradation of EFB supplemented with Trichoderma and organic N was examined, and the compost was tested for crop growth under field condition. The results showed that most of the Trichoderma isolates exhibited an excellent growth performance to cellulose and tannic acid media and had a high ability to utilize different carbon sources. Of the 71 isolates tested, 56 isolates formed a clearing zone between 60-80 mm (75-100 % of Petri dish diameter) on Avicel substrate. Thirteen isolates had clearing zones between 40-60 mm (50-75 % of Petri dish diameter) and two isolates between 20-40 mm (25-50 % of Petri dish diameter). While on CMC substrate, 68 isolates formed a clear zone between 60-80 mm (75-100 % of Petri dish diameter) and three isolates formed between 40-60 mm (50-75 % of Petri dish diameter). Besides, 68 isolates could form dark brown color on tannic acid medium. Thus, they were able to decompose cellulose and synthesized polyphenol oxidase. Cluster analysis identified four clusters of the isolates with the ability to degrade cellulose and tannic acid. Based on this analysis, it was observed that 60 isolates had high ability to degrade carbon sources. From the EFB decomposition test, six selected isolates could decrease carbon and increased nitrogen contents at 3 until 6 weeks of decomposition thus leading to a decrease in C/N ratio and was significantly different compared to control. The decrease in C/N ratios of isolates T24 (T. harzianum) and T43 (T. koningii) were higher than those of other isolates. These isolates also did not posses any harmful characters detrimental to the crop plants, based on the plant performance against fungal biomass (FBM) and fungal metabolite (FM) tests. Therefore, T24 and T43 were selected as the best potential isolates for rapid composting of EFB. Biodegradation of EFB supplemented with Trichoderma and organic N (chicken manure) gave significant changes compared to Trichoderma or chicken manure alone. Supplementation Trichoderma and chicken manure resulted in a higher decrease in the percentage of cellulose (50.35 - 56.07) and hemicellulose (58.50 - 62.43). The C/N ratio, Germination Index of tomato seeds, and plant growth of tomato profiles showed that the compost had reached a satisfactory level of maturity on the 28" day of composting, and was acceptable for application to soil. The contents of N, P, K, Ca, and Mg of the 28 day-old EFB compost treated with Trichoderma and chicken manure were 2.19 - 2.3296, 1.35 - 1.48%, 3.99 - 4.08% 3.49 - 3.67% and 1.41 - 1.63%, respectively, and have significant inorganic fertilizer replacement value for these major plant nutrients. Under field condition, it showed that application of EFB compost significantly improved the soil chemical and biological characteristics and also significantly increased plant growth and yield. Application of EFB compost at a rate of 15 tha seemed to be optimum for dry weight of tomato on the first planting and grain yield of corn on the second planting. Results of this test also indicated that EFB compost and chicken manure at the same rate (7.5 t/ha), respectively induced a similar effect in the soil and plant growth. This means that EFB compost could be as good as chicken manure for crop cultivation.